Penerapan Metode Technology Readiness Index Untuk Mengukur Tingkat Kesiapan Anak Sekolah Dasar Melakukan Pembelajaran Berbasis Online Pada SD Muhammadiyah 09 Plus - Fandi Ahmad; Eni Pudjiarti; Eka Puspita Sari (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Technology continues to evolve all the time, in order to keep up with the development of technology, students must continue to update their knowledge in the field of technology if they do not want to miss, we must continue to develop learning methods so that learning is comfortable and at the same time not behind the times and technology, one of which is online-based learning. (e-learning) which is already familiar today, SD Muhammadiyah 09 Plus, located in Duren Sawit, East Jakarta, is one of the schools that implements e-learning as one of its learning support systems, in its application, a research is needed to determine the level readiness of SD Muhammadiyah 09 Plus in implementing e-learning using the Technology Readiness Index (TRI) method. This method uses an index to measure the level of readiness of users in using new technology to achieve goals in everyday life. There are variables used in this method to measure readiness, namely optimism, innovation, discomfort, and insecurity. The data were obtained from 105 respondents consisting of teachers and guardians of students who produced a TRI score of 2.48 which was categorized in the medium technology readiness index, thus SD Muhammadiyah 09 Plus was ready to implement e-learning by taking into account the discomfort and insecurity variables which still received low scores 0,30 and 0.61.